2018
DOI: 10.1097/meg.0000000000001003
|View full text |Cite
|
Sign up to set email alerts
|

Shear-wave elastography for the assessment of liver fibrosis in liver transplant recipients treated for hepatitis C virus recurrence

Abstract: In the present study, SWE was succesfully used to monitor the beneficial therapeutic effects of direct-acting antivirals in hepatitis C recurrence following liver transplantation. We believe that SWE is a useful noninvasive diagnostic tool in the follow-up of hepatitis C treatment in liver transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The same was true for APRI and FIB-4 indexes that showed significant improvement at 24 and 48 weeks after therapy. Similar to our results, another recently published article [30] that evaluated 23 LT patients with recurrent HC treated for 24 weeks with OBV/PTV/r+DSV±RBV combination therapy, showed that shear-wave elastography and also APRI and FIB-4 were successfully used to monitor the beneficial therapeutic effects of DAAs in hepatitis C recurrence following LT. Mauro et al [31] proved that 67% of the cohort presented fibrosis regression; HVPG, liver stiffness and ELF score significantly decreased after SVR. There are also few previous studies [32][33] reporting histological and clinical benefits, associated with improvement of patient and graft survival after SVR in LT recipients.…”
Section: Discussionsupporting
confidence: 89%
“…The same was true for APRI and FIB-4 indexes that showed significant improvement at 24 and 48 weeks after therapy. Similar to our results, another recently published article [30] that evaluated 23 LT patients with recurrent HC treated for 24 weeks with OBV/PTV/r+DSV±RBV combination therapy, showed that shear-wave elastography and also APRI and FIB-4 were successfully used to monitor the beneficial therapeutic effects of DAAs in hepatitis C recurrence following LT. Mauro et al [31] proved that 67% of the cohort presented fibrosis regression; HVPG, liver stiffness and ELF score significantly decreased after SVR. There are also few previous studies [32][33] reporting histological and clinical benefits, associated with improvement of patient and graft survival after SVR in LT recipients.…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, various SWE techniques are gaining wide acceptance among clinicians as a noninvasive tool for the detection and precise staging of fibrosis and cirrhosis, which are very important for the timely initiation of appropriate therapeutic regimens [14]. Furthermore, the SWE technique could be widely used for monitoring liver fibrosis after the application of antiviral agents [26,27]. Therefore, for the longitudinal assessment or monitoring of liver fibrosis, the interchangeability of LS measurements made using different SWE techniques could be of significant value.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we could acquire liver biopsies from only 9 patients, and only 8 patients had clinically diagnosed cirrhosis. In addition, 4 patients with cirrhosis had been successfully treated for HCV; according to a recent study, the fibrosis stage decreases when HCV treatment eliminates HCV in the patient (Korda et al 2018). Thus, the fibrosis stages of those 4 patients were somewhat unclear.…”
Section: Discussionmentioning
confidence: 99%